Cut both ways - Mesrobian, Carrie (2015)
"Senior Will Caynes must face unsettling feelings for his best friend Angus after they share a drunken kiss, while also embarking on his first real relationship with sophomore Brandy--all as the burden of home-life troubles weigh heavily"--
Keywords: Interpersonal relations -- Juvenile fiction; Bisexuality -- Juvenile fiction; Friendship -- Juvenile fiction; Gays -- Juvenile fiction; Sex -- Juvenile fiction; Young adult fiction; Electronic books